Expenses and Profits of Limited Price Variety Chains in 1939 (Book). - Bice, Hubert E. (The Accounting Review, 1941)
Reviews the book "Expenses and Profits of Limited Price Variety Chains in 1939," by Elizabeth A. Burnham.